Theoretical modeling of RF ablation with internally cooled electrodes:Comparative study of different thermal boundary conditions at theelectrode-tissue interface - María J. Rivera; Juan A. López Molina; Macarena Trujillo; Enrique J. Berjano (Mathematical Biosciences and Engineering)
Previous studies on computer modeling of RF ablation with cooledelectrodes modeled the internal cooling circuit by setting surfacetemperature at the coolant temperature (i.e., Dirichlet condition,DC). Our objective was to compare the temperature profilescomputed from different thermal boundary conditions at theelectrode-tissue interface. We built an analytical one-dimensionalmodel based on a spherical electrode. Four cases were considered:A) DC with uniform initial condition, B) DC with pre-coolingperiod, C) Boundary condition based on Newton's cooling law (NC)with uniform initial condition, and D) NC with a pre-coolingperiod. The results showed that for a long time ($120$ s), theprofiles obtained with (Cases B and D) and without (Cases A and C)considering pre-cooling are very similar. However, for shortertimes ($<30$ s), Cases A and C overestimated the temperature atpoints away from the electrode-tissue interface. In the NC cases,this overestimation was more evident for higher values of theconvective heat transfer coefficient ($h$). Finally, with NC, when$h$ was increased the temperature profiles became more similar tothose with DC. The results suggest that theoretical modeling of RFablation with cooled electrodes should consider: 1) the modelingof a pre-cooling period, especially if one is interested in thethermal profiles registered at the beginning of RF application;and 2) NC rather than DC, especially for low flow in the internalcircuit.